IMPLEMENTASI PENDEKATAN SEGITIGA RESTITUSI DALAM MEMBENTUK DISIPLIN POSITIF SISWA DI SDN 21 PALEMBANG - Saputra, Josa; Yanti, Salika Wardama; Ayisa, Selpia Putri; Yulaini, Erma; Utomo, Budi; Kusumawati, Nila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The formation of positive discipline is an important part of student character education. The restitution triangle approach, which emphasizes reflection, admitting mistakes, and self-improvement, is considered effective in improving discipline without relying on punishment or rewards. Although SDN 21 Palembang has implemented positive discipline, there are still violations of rules by students. Therefore, a more optimal approach is needed that touches on the aspect of self-awareness. This study aims to describe the implementation of the restitution triangle in forming positive student discipline. This study aims to describe the implementation of the restitution triangle approach in forming positive student discipline and the obstacles faced by class V-B teachers at SDN 21 Palembang. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through observation, interviews, documentation, and questionnaires. Data analysis for this study is based on the Miles and Huberman model. Activities included in the data analysis for this study are data reduction, data presentation, and drawing conclusions. The results of the study indicate that the restitution triangle consisting of three stages of stabilizing identity, validating wrong actions, and asking for beliefs has succeeded in increasing students' awareness of discipline and responsibility. The obstacles encountered include differences in student character, students' lack of initial understanding of the rules, and teachers' time constraints. However, through this approach, a positive and reflective learning environment can be created.